ЎРТА ЁШДАГИ ИШСИЗ АҲОЛИНИ ИШ БИЛАН ТАЪМИНЛАШ МУАММОЛАРИ ВА ЕЧИМЛАРИГА БИР НАЗАР (Scientific journal of the Fergana State University, 2023)
This article is about social protection and increase status in employment of population in Uzbekistan, especially increase the role of universities in training and retraining unemployment middle age generation.